Management of Grazed Landscapes to Increase Soil Carbon Stocks in Temperate, Dryland Grasslands - Whitehead, David (Frontiers in Sustainable Food Systems, 2020)
Management of the temperate, grazed grasslands in New Zealand for more than a century has led to swards dominated by ryegrass/clover, which, with inputs of inorganic fertilizers, are highly productive for grazing animals. In the last 20 years the widespread introduction of irrigation to dryland areas on flat land has increased productivity further. However, these intensive practices decrease soil carbon stocks. In contrast, there is limited evidence that improved management of dryland, grazed, hill country grasslands can lead to increases in soil carbon stocks. To address global needs for food security and climate change mitigation, priority actions to increase soil carbon stocks need to focus on improved management practices to increase carbon inputs and retention in soils identified as having high potential for increasing carbon storage. While there are limited data from New Zealand studies, international observations suggest that soil carbon stocks can be increased by enhancing below-ground carbon inputs from plants with deep roots, using swards with diverse species, and moderate grazing rather than harvesting biomass. However, there is less certainty about the processes regulating the formation and decomposition of soil organic matter and their dependence on soil physical properties and microbial access. Scaling findings from plot studies to forecast long-term changes in soil carbon stocks at the landscape scale can be done using models but new approaches are required to integrate the impacts of multiple concurrent practices associated with grazing management.